Design of multi-key encryption method - Yuqing ZHONG; Hao WANG; Zebing LIN; Min WANG; Liye CHEN (Dianxin kexue)
In order to improve the security in the process of information transmission,the current encryption methods were studied,and the research status was reported which increased the security of encryption by processing the key.According to the principle of segmenting and grouping data in the process of sending and encrypting,a method of multi-key encryption was designed:the segmenting key group and grouping key group were generated by the source key and random number,and the corresponding key was selected for each segmented and grouped data by its sequence number according to the matching algorithm.This method realized the encryption of multi-key in the process of information transmission.Finally,on the one hand,MATLAB was used to test and verify the encryption efficiency of this method.On the other hand,the security of this method was analyzed from the theoretical and mathematical perspective,comparing with the traditional method.It is concluded that this method can increase the security of the traditional method without too much cost much cost.